2015
DOI: 10.1007/s00330-015-3990-y
|View full text |Cite
|
Sign up to set email alerts
|

Using intravoxel incoherent motion MR imaging to study the renal pathophysiological process of contrast-induced acute kidney injury in rats: Comparison with conventional DWI and arterial spin labelling

Abstract: • IVIM analysis permits separate quantification of diffusion and perfusion. • IVIM can provide useful biomarkers ifor changes in renal pathophysiology. • IVIM can be useful for monitoring progress in renal pathophysiology undergoing CIAKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 35 publications
1
42
0
1
Order By: Relevance
“…Diffusion-weighted imaging and ADC measurement can offer quantitative information on the microstructure and water motion on a molecular level 10, 13, 14, 18, 19 . Although ADC measurement with conventional monoexponential model delivers signals from both capillary perfusion and extracellular diffusion, measurement of ADC with b -values > 400 sec/mm 2 primarily referring to molecular water diffusion for blood perfusion signals are substantially suppressed by the large diffusion gradients 13, 14, 26, 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffusion-weighted imaging and ADC measurement can offer quantitative information on the microstructure and water motion on a molecular level 10, 13, 14, 18, 19 . Although ADC measurement with conventional monoexponential model delivers signals from both capillary perfusion and extracellular diffusion, measurement of ADC with b -values > 400 sec/mm 2 primarily referring to molecular water diffusion for blood perfusion signals are substantially suppressed by the large diffusion gradients 13, 14, 26, 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Although ADC measurement with conventional monoexponential model delivers signals from both capillary perfusion and extracellular diffusion, measurement of ADC with b -values > 400 sec/mm 2 primarily referring to molecular water diffusion for blood perfusion signals are substantially suppressed by the large diffusion gradients 13, 14, 26, 27 . In the present study, 7 b-valves (0, 50, 150, 450, 650, 850, and 1000 sec/mm 2 ) were used for calculating ADC avg , and the gradients were applied in three orthogonal directions and subsequently averaged so that the effects of diffusion anisotropy could be eliminated 26, 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing IVIM fD * and ASL blood flow are sparse and inconclusive. In the rat kidney cortex Liang et al found an excellent correlation between fD * and ASL blood flow (0.803, p < 0.0001), while in stroke patients Yao et al found a weak correlation between fD * and ASL cerebral blood flow ( r = 0.39, p = 0.0002), and in the brain of healthy volunteers Wu et al found no correlation between these two parameters.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…IVIM is a four‐parameter model that assumes two compartments with pure water diffusion and directional flow. Variations in the diffusion and perfusion parameters over time may provide a means for uncovering early pathophysiological changes in acute renal injury after transplantation or contrast injection . Although perfusion parameters can be acquired from IVIM models, they are weakly correlated with the parameters derived from DCE‐MRI, such as the GFR and the mean transit time (MTT).…”
Section: Renal Fmrimentioning
confidence: 99%